Oxidative fluorination with Selectfluor: A convenient procedure for preparing hypervalent iodine(V) fluorides - Dearman, Samuel M. G.; Li, Xiang; Li, Yang; Singh, Kuldip; Stuart, Alison M. (Beilstein Journal of Organic Chemistry, 2024)
The ability to investigate hypervalent iodine(V) fluorides has been limited primarily by their difficult preparation traditionally using harsh fluorinating reagents such as trifluoromethyl hypofluorite and bromine trifluoride. Here, we report a mild and efficient route using Selectfluor to deliver hypervalent iodine(V) fluorides in good isolated yields (72–90%). Stability studies revealed that bicyclic difluoro(aryl)-λ5-iodane 6 was much more stable in acetonitrile-d3 than in chloroform-d1, presumably due to acetonitrile coordinating to the iodine(V) centre and stabilising it via halogen bonding.
Keywords: fluorination; fluorobenziodoxoles; halogen bonding; hypervalent iodine; Selectfluor